Appendiceal mucocele masquerading as an epithelial borderline ovarian tumor: A case report from Somalia - Muse, Nuur Mucaawiye; Said, Abdirahman Ibrahim; Mohamed, Ismail; Hussein, Abdilahi; Hussein, Mohamed Omer; Elmi, Hassan Sh Abdirahman (International journal of surgery case reports, 2024)
INTRODUCTION: Appendiceal mucocele, a rare condition characterized by mucoid material accumulation in the appendix, often presents asymptomatically. Diagnosis can be challenging, and surgical resection is crucial to prevent complications. We report a case managed in a low-resource setting, highlighting the importance of early identification. CASE PRESENTATION: A 56-year-old postmenopausal woman presented with right lower quadrant pain and a pelvic mass. Imaging revealed a cystic lesion and exploratory laparotomy was performed. Intraoperatively, a mucocele of the appendix was discovered. An appendectomy was performed, and a histopathological examination confirmed a serous borderline tumor, this work has been reported in line with the SCARE criteria. DISCUSSION: Preoperative diagnosis of appendiceal mucoceles is difficult due to their clinical variability. Surgical intervention is essential, with meticulous resection required to prevent peritoneal contamination. The absence of intraoperative pathology consultation in this case underscores the need for greater access to specialized resources, including pathology services, in resource-limited settings to ensure accurate diagnosis and appropriate surgical management. CONCLUSION: This case highlights the critical importance of clinical suspicion for appendiceal mucoceles, even when initial radiological findings are inconclusive. The lack of intraoperative pathology consultation underscores the need for specialized pathology services in resource-limited settings. Given the increased risk of colonic adenocarcinoma, multidisciplinary collaboration and diligent post-operative surveillance are crucial for optimizing patient outcomes.